Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Klinik Saintifikasi Jamu "Hortus Medikus" Tawangmangu - Permata Sari, Lina; , Jati Waskito SE., M.Si (2016)
This research aims to find out and analyse the extent of the influence of the quality of the services against the level of satisfaction felt by customers who use the service on Saintifikasi herbal medicine Clinic "Hortus Medikus" in Tawangmangu. The model used in this study is a method of observation, interview, questionnaire, and studies using likert scale libraries and methods of determination of the sample used is aksidental sampling as much as 100 samples. Methods of analysis used was multiple linear regression methods (linear multi regression). The research of service quality of Reliability (X 1), Responsiveness (X 2), Assurance (X 3), Emphaty (X 4) and Tangible (X 5) shows that from the results obtained show the regression koefesien, variable emphaty (X 4 =-0.410) became the biggest factor with significant figures-a second variable, 7.576 assurance (X 3 = 0.327) with significant numbers of variable reliability, third 6.067 (X 1 = 0.239) with a significant number of the fourth variable, 3.255 tangible (X 5 = 0.194) with significant numbers 3.463 the fifth variable, ressponsiveness (X 2 = 0.207) with a significant number being the lowest factor of 2.235 affect customer satisfaction. Where the regression equation Y = 4.932 + 0, 239X1 + 0, 207X2 + 0, 327X3-0, 410X4 + 0, 194X5 + 1.569. In addition, the F-test with views that quality service have significant influence towards customer satisfaction with the level of significance of 0.000 or 0%. But based on the partial test (t), all variables have significant influence towards customer satisfaction with the significant level for the Reliability of 0.002 or 0.2%; Responsiveness of 0.045 or 4.5%; Assurance of 0.000 or 0%; Emphaty 0.000 or 0% and Tangible of 0.001 or 0.1%.